Problematika Guru Ber-Kompetensi Tidak Terlatih Terhadap Kemajuan Sekolah - Ernawati Nehe (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2020)
Research on teacher competency problems that were not attained in this school used qualitative methods. The descriptions compiled from this study are based on data collection in the form of books, scientific journals and the results of relevant research that have been done before. Then do the formulation of the problem, analyze the data and identify until verified research results are obtained. The result is that teachers who already have competence but are less trained in school will cause problems in increasing the quality and competition in the world of education. This is increasingly felt with the presence of revolution 4.0 in the world of education which demands creative and innovative teachers not only fulfilling formal competences. The world of teaching and education in schools now has to answer the challenges of advances in information and science technology itself and the ever-changing learning applications. The conclusion obtained from this research is that the teaching profession in this era must have more professional awareness and responsibility, and must not stop to improve the quality of competence by increasing training